2015
DOI: 10.1002/hep.27927
|View full text |Cite
|
Sign up to set email alerts
|

Absence of the intestinal microbiota exacerbates hepatobiliary disease in a murine model of primary sclerosing cholangitis

Abstract: Introduction Primary sclerosing cholangitis (PSC) is a chronic, idiopathic, fibro-inflammatory cholangiopathy. The role of the microbiota in PSC etiopathogenesis may be fundamentally important yet remains obscure. We tested the hypothesis that germ-free (GF) mdr2−/− mice develop a distinct PSC phenotype compared to conventionally-housed (CV) mdr2−/− mice. Methods Mdr2−/− mice (n=12) were re-derived as GF by embryo transfer, maintained in isolators, and sacrificed at 60 days in parallel with age-matched CV md… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
140
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(149 citation statements)
references
References 50 publications
6
140
2
1
Order By: Relevance
“…Investigators observed an increase in mucosal Barnesiellaceae at the family level and Blautia at the genus level. Germ-free, multidrug resistance 2 knockout mice (mdr2 −/− mice) show exacerbated biochemical and histological features of PSC and increased cholangiocyte senescence further supporting the notion that gut microbiota might play a role in disease process 65. Interestingly, primary bile acids were similar, whereas secondary bile acids were absent in germ-free mdr2 −/− mice.…”
Section: Primary Sclerosing Cholangitis and Microbiotamentioning
confidence: 78%
“…Investigators observed an increase in mucosal Barnesiellaceae at the family level and Blautia at the genus level. Germ-free, multidrug resistance 2 knockout mice (mdr2 −/− mice) show exacerbated biochemical and histological features of PSC and increased cholangiocyte senescence further supporting the notion that gut microbiota might play a role in disease process 65. Interestingly, primary bile acids were similar, whereas secondary bile acids were absent in germ-free mdr2 −/− mice.…”
Section: Primary Sclerosing Cholangitis and Microbiotamentioning
confidence: 78%
“…Hepatotoxins cause more liver injury and fibrosis in germ-free than in wild-type mice [78]. Consistently, a mouse model of primary sclerosing cholangitis shows exacerbated hepatobiliary damage under germ-free conditions [79].…”
Section: Intestinal Dysbiosis and Bacterial Translocation Initiate Anmentioning
confidence: 97%
“…7 Data from basic and clinical studies have long supported the hypothesis that the intestinal microbiota may have a role in PSC pathogenesis. [8][9][10] Recently, studies using next-generation sequencing have reported a distinct fecal or mucosal microbiota composition in PSC-IBD patients. [11][12][13][14][15][16][17][18] There is a close interplay between gut flora and BA metabolism.…”
Section: Introductionmentioning
confidence: 99%